Overview and Analysis of Health Law Number 17 of 2023 - Asrina Wijayanti (Enigma Institute, 2023)
Health Law No. 17/2023 is significant legislation aimed at enhancing the caliber of the healthcare system in Indonesia. This legislation introduces novel guidelines for overseeing the healthcare system, emphasizing elements such as disease prevention, availability of healthcare services, the ability to withstand health challenges, and effectiveness and openness in healthcare funding. In order to effectively execute Health Law No. 17/2023, it is imperative that all stakeholders, including the central government, regional governments, communities, and the corporate sector, demonstrate commitment and cooperate with one another.